propioceptive neuromuscular facilitation technique versus kinesiotaping on lymphedema after mastectomy - Amany Waheed Abdelsalam; Nancy Hassan Aboelnour; Samah Hosny Naguib; Samy Ramzy Shehata (Cairo : Amany Waheed Abdelsalam, 2017)
Purpose: This study was designed to compare the therapeutic effect of the Proprioceptive Neuromuscular Facilitation technique and Kinesiotaping on lymphedema after mastectomy. Participants: Thirty patients who have lymphedema post mastectomy participated in this study. Their ages ranged from 40-55 years. The participants were selected from learning hospitals (National Cancer Institute) and randomly distributed into two equal groups: Proprioceptive Neuromuscular Facilitation Technique group and Kinesiotaping technique group for 3 months (3 sessions of 30 minutes/week) and subjects were evaluated before starting the treatment, then after the end of the treatment course. Methods: -Tape measurement to assess the edema volume according to edema equation: V= h x (C2 +Cc +c)/ (s x 12). -Universal goniometer to assess shoulder flexion range of motion. Results: The results of the study were recorded as both the Proprioceptive Neuromuscular Facilitation technique and kinesiotaping applications had the same significant improvement on arm lymphedema post mastectomy and Proprioceptive Neuromuscular Facilitation technique was more effective than kinesiotaping application in shoulder flexion range of motion. Conclusion: Both Proprioceptive Neuromuscular Facilitation technique and kinesiotaping applications use in treatment program affecting on lymphedema post mastectomy
Thesis (M.Sc.) - Cairo University - Faculty of Physical Therapy - Department of Physical Therapy for Surgery
Issued also as CD
Keywords: Kinesiotaping; Lymphedema; Proprioceptive Neuromuscular Facilitation Technique